PENGARUH MODEL PEMBELAJARAN JOYFUL LEARNING TERHADAP KREATIVITAS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 2 KOTA BOGOR - Ismi Khairunisa; Muhamad Azhar Alwahid; Andestend (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of the Joyful Learning model on improving students' creativity in Islamic Religious Education (PAI) at SMAN 2 Kota Bogor. PAI learning has often been considered monotonous and unengaging, which reduces students' interest and creativity, while the growing influence of secularism further weakens the relevance of religious values in students' daily lives. This research employed a quantitative approach with a Quasi-Experimental design. The sample consisted of 84 grade X students at SMAN 2 Kota Bogor, divided into an experimental class (X6, 41 students) and a control class (X8, 43 students) selected through cluster sampling. Data were collected using a creativity test, a Likert-scale questionnaire, observation, and documentation, then analyzed using descriptive statistics, normality and homogeneity tests, and the Mann-Whitney U test with the assistance of SPSS. The results showed that the mean creativity score of the experimental class was slightly higher than that of the control class; however, the Mann-Whitney U test indicated no significant difference between the two groups (Asymp. Sig. (2-tailed) = 0.996 > 0.05). These findings suggest that the Joyful Learning model has not yet produced a significant effect on improving students' creativity, although it continues to contribute positively to increasing students' motivation and engagement in PAI learning.